Compare the effect of art therapy and play therapy in reducing anxiety among hospitalized preschool children in selected hospitals - Dalei, S.R.; Nayak, G.R. (Journal of Biomedical Sciences, 2019)
Background: Children are very precious being. The multidimensional refinement occurs during preschool period. Hospitalizations lead to anxiety and strain for children. Play and art are tremendous method of communication, expansion of social relationship, express emotion and eventually lead to a new value added life styles. Material and methods: This study focus on comparing the effect of art therapy and play therapy in reducing anxiety among hospitalized preschool children in selected hospitals of Bhubaneswar by quantitative experimental research approach of True experimental pretest – posttest only design. 60 preschool children were selected by using simple random sampling technique. Data collected through Self-structured Questionnaire on sociodemographic and Self-structured hospitalization anxiety scale. Collected data analyzed by using descriptive and inferential statistics. Result: The study findings revealed that 75% children had moderate anxiety, whereas 5% had mild anxiety among hospitalized preschool children. There was significant difference observed between pre-test and post-test mean score of anxiety level both in art and play therapy at p<0.0001. In comparison of post-test result by Anova of anxiety level between art therapy play therapy and control group showed that mean score of post-test of play therapy (1.95), art therapy (2.1) and control group (2.25) of anxiety level. The significance value is 0.025 (i.e., p = .025), which is below 0.05, therefore, there is statistically significant difference in the anxiety level between the different groups. Play therapy is more effective than art therapy. Chi-square statistics was used, there was notable association between duration of hospitalization and anxiety level at χ2 =10. Conclusion: It concludes that hospitalization creates a negative impact on the development of the child. Art therapy and Play therapy is more acceptable and can include in normal routine activities. It is cost effective, convenient, requires less skills.